Academic writing challenges faced by chemistry doctoral students: A self-study informed by three writing theories - Ead, Hamed A.; Fahmy, Heba; Elbadry, Abdallah (Association for Scientific Computing Electrical and Engineering(ASCEE), 2023)
This research investigated the challenges faced by chemistry Ph.D. candidates writing in English as a second language. Drawing from Second Language Writing, Genre Theory, and Academic Writing Instruction and Support, we investigated the linguistic, cultural, and disciplinary factors that might affect these students' writing development. Nineteen doctoral students participated in the study, which relied on a self-study methodology. Attitudes towards writing, idea generation, revision, criticism, cooperation, and writing process awareness were only some topics covered in a seven-part online survey on academic writing. Language, method, outcomes, style, and substance were found to be the most salient aspects of academic writing as seen by graduate students. There were five major classes of issues with academic writing, including text, errors, competence, support, and dissemination medium. By drawing on the fields of Second Language Writing, Genre Theory, and Academic Writing Instruction and Support, we propose strategies for enhancing students' abilities in academic writing. These strategies range from providing more detailed instructions on the writing process to emphasizing the importance of close communication between faculty advisors and their students. The ramifications of these results for graduate education programs that want to help their students with their academic writing are substantial.